Deracemisation processes employing organocatalysis and enzyme catalysis - Aranda Álvarez, María del Carmen (2020)
Deracemisation methods have demonstrated their importance in the preparation of chiral compounds in the last few years. In order to resolve a racemic mixture in a dynamic sense, one enantiomer of the starting material can be converted to the other through a deracemisation procedure, that can be achieved by different mechanisms based on stereoinversion or enantioconvergence, often involving two-opposite half reactions, with at least one of the reactions being enantioselective enough to finally obtain an enantioenriched chiral compound. The focus of this comprehensive review is on the application of deracemisation procedures in the present century in order to obtain optically active valuable compounds when employing non-metallic catalysts. Thus, the review will mainly focus on the use of different enzymatic preparations (purified enzymes, cell-free extracts or whole cell systems) and organocatalysts for the deracemisation of racemic mixtures. (Figure presented.).